Alternatif Perancangan Pondasi Tiang Pancang Sebagai Pengganti Pondasi Tiang Bor Pada Konstruksi Pile Slab - Windi Ismail; Arman Setiawan; Eka Yuniarto (Program Studi Teknik Sipil Universitas Bosowa, 2026)
Pile foundations are widely used in construction, particularly for structures on low-bearing capacity soils or heavy buildings. Driven and bored piles are the most common types. This study explores driven piles as an alternative to bored piles, focusing on foundation strength through bearing capacity comparison. The selected driven pile is a prestressed precast concrete pile, 1 meter in diameter and 14 meters deep. The method involves calculating bearing capacity using the Meyerhoff equation based on N-SPT data, along with analyzing pile reactions and displacement at the supports through displacement analysis. The calculation results show that the carrying capacity of piles with a diameter of 1 m and a depth of 14 m reaches 2861 kN, larger than a drilled pile with a diameter of 0.8 m and a depth of 21 m with a carrying capacity of 1895.1 kN. Based on these results, prestressed spun pile concrete piles were selected with a concrete quality of fc' 50 MPa, a diameter of 1 m, and a total length of 21 m. The selection of this alternative based on the results of the analysis is still within the safe limit so that the foundation is safe to use.